Lifelong learning practices of primary school teachers: a systematic literature review - Mohd, Ros Faizah; Zulkifli, Hafizhah; Hamzah, Mohd Isa (Institute of Advanced Engineering and Science, 2024)
The practice of lifelong learning among teachers involves continuous efforts to enhance their knowledge, skills, and competencies through various activities. Previous studies have explored different practices such as reading, collaboration, participation in courses, culturalizing learning, conducting research, and digital learning. However, there is a lack of systematic reviews of these practices. This an article aims to fill this gap by conducting a systematic review of lifelong learning practices among primary school teachers for 5 years since 2019 until 2023. The study integrates various research designs and follows the ROSES publication standard. Articles were selected from databases including Scopus, Web of Science (WoS), and ERIC. Thematic analysis revealed four key concepts: self-learning, continuous training, knowledge integration, and digital networks. Future research can focus on examining the resilience of teachers from diverse backgrounds in adapting to changes in the education system. This study serves as a valuable reference for teachers to assess their own lifelong learning practices and facilitate transformative growth towards becoming knowledgeable educators